Acromicric dysplasia with stiff skin syndrome‐like severe cutaneous presentation in an 8‐year‐old boy with a missense FBN1 mutation: Case report and literature review. Issue 7 (14th May 2020) - Wang, Tao; Yang, Yuyan; Dong, Qi; Zhu, Huijuan; Liu, Yuehua
Abstract: Background: Acromicric dysplasia is a rare heritable short‐stature syndrome with joint stiffness and varying degrees of cutaneous hardness. Stiff skin syndrome is a rare connective tissue disorder characterized by diffusely thick and hard skin from the time of birth. Heterozygous point mutations in the FBN1 have been proposed as the predominant cause of both diseases. Methods: By performing skin biopsy, X‐ray imaging, electrocardiography, as well as whole‐genome sequencing and Sanger sequencing, we diagnosed an 8‐year‐old Chinese boy as acromicric dysplasia with severe skin stiffness caused by a heterogeneous mutation in the FBN1 . Results: The patient presented with skin tightness, wrist and ankle stiffness, short stature and limbs, several deformed joints in the extremities, cone‐shaped epiphyses, and distinct facial features. He also had a patent foramen ovale and frequent respiratory infections. Skin biopsy showed thickened dermis and excessive collagen aggregation. Alcian blue staining indicated dermal mucopolysaccharide deposition. Mutation analysis revealed a heterozygous missense mutation, c.5243G>A (p.Cys1748Tyr), in exon 42 of the FBN1 . Conclusion: This is a report about acromicric dysplasia with stiff skin syndrome‐like severe cutaneous presentation caused by a single hotspot mutation, further revealing the gene pleiotropy of FBN1 . Abstract : This study reports about the coexistence of stiff skin syndrome‐like severe cutaneous presentation and acromicric dysplasia in a single patient caused by a single hotspot mutation, further revealing the gene pleiotropy of FBN1 .